Effect Of Alkaline Earth Metal Cations Incorporation On The Self-Assembly Of Mesoporous Silica: Physicochemical Study And Catalysis Of Styrene - Tan, Kok Hou (2021)
Three series of alkaline earth metal (magnesium, calcium and barium) mesoporous silicate catalysts were prepared via direct one-pot synthesis by varying the metal to surface directing agent (CTAB) molar ratio (0.25, 0.50, 0.75 and 1.00) Characterization results indicate that the physicochemical properties of the resulting catalysts depend on the size of the alkaline earth metal cations and metal/CTAB molar ratios. The incorporation of the alkaline earth metals in the silica framework disrupted the arrangement of pore channels and increased pore size compared to parent silica (MST). The alkaline earth metal species on the catalyst's surface varies according to the metal/CTAB molar ratio. Liquid phase epoxidation of styrene in the presence of prepared alkaline earth metal catalysts have produced styrene oxide (StO) as the major product and benzaldehyde (PhCHO) and phenylacetaldehyde (PA) as the minor products. In general, the highest catalytic activity was observed at a metal/CTAB ratio of 1.00. Mesoporous 1.00CaMST performed the best by achieving the highest styrene conversion (66.9%) and StO selectivity (79.2%) at mild temperature (60 °C) and a lower catalyst loading (100 mg). The activation energy of 1.00CaMST (10.9 kJ mol-1) is also found to be lower than 1.00MgMST (27.7 kJ mol-1) and 1.00BaMST (17.3kJ mol-1). The reactions were found to fit better to the pseudo-first order kinetic model. The mechanism of the catalysed reaction was proposed based on the type of alkaline earth metal surface active sites.